2014
DOI: 10.1089/ars.2013.5368
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Confers Protection in Sepsis by Enhancing Beclin 1-Dependent Autophagy and Phagocytosis

Abstract: CO increases the survival of mice injured by CLP through systemic enhancement of autophagy and phagocytosis. Taken together, we suggest that CO gas may represent a novel therapy for patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 50 publications
3
102
1
Order By: Relevance
“…As the biallelic loss of BECN results in embryonic lethality, we used MSCs from BECN1 heterozygous knockout mice. These mice have previously been validated to have impaired autophagy (18,20). Both LC3B and BECN1 represent core autophagy proteins, even though they differ in their role in autophagy regulation.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As the biallelic loss of BECN results in embryonic lethality, we used MSCs from BECN1 heterozygous knockout mice. These mice have previously been validated to have impaired autophagy (18,20). Both LC3B and BECN1 represent core autophagy proteins, even though they differ in their role in autophagy regulation.…”
Section: Original Researchmentioning
confidence: 99%
“…Among the numerous autophagy-related genes that have been identified, beclin 1 (Becn1), plays a critical regulatory function in the initiation of the autophagic pathway (18). It is important for the nucleation of autophagosomes (19).…”
mentioning
confidence: 99%
“…Conversely, knocking out Becn1 renders the mice more susceptible to septic injury and unresponsive to carbon monoxide therapy. 10 A helminth product, ES-62, also downregulates TLR2-and TLR4-driven inflammatory responses by enhancing MYD88-dependent autophagosome formation. 21 The mechanisms of protective effect of autophagy activation in sepsis remain to be elucidated.…”
Section: Microbe-host Interactions and Autophagymentioning
confidence: 99%
“…8 Further ex vivo experiments revealed that the mRNA expression of IRGM is significantly lower in the TT genotype, rendering it defective in autophagy. 8 Accumulating evidence from in vitro and in vivo studies [9][10][11][12][13][14][15] suggest that autophagy plays a protective role in sepsis, although contradictory findings have been reported. 16,17 In support of this notion, newly tested therapeutic agents in animal models have targeted modulation of the same molecular pathway-autophagy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation